2011
DOI: 10.2298/tsci100225058p
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of Scheffler reflector water heater

Abstract: The performance of Scheffler reflector has been studied. In this system storage reservoir was installed at Focus point. It has a single large diameter drum which serves the dual purpose of absorber tube and storage tank. The drum is sized to have a storage capacity of 20 liter for experiment. The tests were carried out with this set up and were repeated for several days. Performance analysis of the collector has revealed that the average power and efficiency in terms of water boiling test to be 1.30 kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The strenuous energy is multi-purpose and could be used for heating 54 an oven to 180-250 C in an hour while keeping the temperature constant. This focused energy from several combined reflectors could be utilized for the steam generation.…”
Section: Significance Of Solar Reflectorsmentioning
confidence: 99%
“…The strenuous energy is multi-purpose and could be used for heating 54 an oven to 180-250 C in an hour while keeping the temperature constant. This focused energy from several combined reflectors could be utilized for the steam generation.…”
Section: Significance Of Solar Reflectorsmentioning
confidence: 99%
“…Based on the solar reflector performance and durability, it was reported that glass, silvered polymer, and front-surface mirrors can remain for a 10-year lifetime. Performance and applications are detailed in [ 11 ] who conducted an experimental study on a Scheffler reflector with an area of 8 m 2 . The study shows that the overall efficiency of the absorber located in the center of the parabolic dish concentrator was 21.61%.…”
Section: Introductionmentioning
confidence: 99%
“…There are also fixed focus and tracking problems present in them [27]. Among the available solar concentrating technologies, the Scheffler fixed-focus concentrator is the best suitable option for generating heat energy in medium to the high-temperature range with a variety of reflector sizes ranging from 2 to 60 m 2 [28][29][30]. The versatility of the Scheffler reflector is the fixed focus at the targeted position by automatically tracking the sun, which provides a uniform temperature distribution on the focus point throughout the day.…”
Section: Introductionmentioning
confidence: 99%